An improved certificateless two-party authenticated key agreement protocol for wireless sensor networks. (9th July 2020) - Deng, Lunzhi
Key agreement is an important way to achieve secure communication between the two or more parties. In the past decade, wireless sensor networks (WSNs) have received great attention and contributed to the development of low-power sensor networks. In WSNs, sensor nodes are generally inexpensive, low-power devices with limited computing and storage capabilities. So it is very valuable to design a secure and efficient key agreement protocol for WSNs. Recently, Bala et al. (2016b) put forward a certificateless two-party authenticated key agreement (CL2PAKA) protocol for WSNs and asserted that it is provably secure in the extended Canetti-Krawczyk (eCK) model. In this paper, by showing the concrete attack, Bala et al's protocol was proved to be vulnerable against the type I adversary. In order to make up for the security flaws, an improved protocol is proposed. It does not require pairing operations and requires only five scale multiplication operations, so it is suit for WSNs.